Estudo do pré-tratamento do bagaço de cana-de-açúcar com ácido acético diluído em sistema pressurizado - Oliveira, Carlos Alberto Petersen de (2016)
Sugarcane bagasse represents an important source of lignocellulosic compounds, which can be converted, by pretreatments, in high added value chemicals, used by materials, paper and pulp, cosmetics, pharmaceutical and energy industries. In this study, sugarcane bagasse (SCB) was pretreated with acetic acid in a batch reactor pressurized. Initially, a comparative study was performed to evaluate the effects caused by pressure over sugarcane bagasse pretreatment. Then, an experimental design evaluated the effects of time (15-100 min), temperature (100-180 ºC), solid-toliquid ratio (1:250 -1:62.5) and acetic acid concentration (1-5 % v/v) over the weight loss, besides sugars and degradation products recovery. Sugarcane bagasse after pretreatment were characterized by elemental, thermogravimetric, X-ray powder diffraction, differential calorimetry scanning and calorific value analysis. The hydrolysates were analyzed by liquid chromatography to quantify the major sugars and degradation products formed. The influence of acetic acid concentration and solidto- liquid ratio were not statistically significant, but time and mostly temperature showed significance over weight loss, xylose recovery and degradation products formation. The response surface analysis revealed that the highest percentages of weight loss and sugars recovery were obtained under conditions of 176 °C / 104 min (SCB1) and 155 °C / 62 min (SCB2), respectively. The use of severe conditions showed greater efficiency in the delignification and recovery of molecules commercially relevant, while milder conditions promoted greater hydrolysis and recovery of sugars. Both pretreatments influenced the crystallinity and the calorific value of the solid residues, an also their thermal stability and surface area. Oxygenated compounds removal from hemicellulose and lignin were also observed. Hydrolysates analysis revealed the formation of products with important commercial interest, such as furfural, hydroxymethylfurfural, lactic, levulinic, glycolic and formic acids, as well as sugars such as xylose, arabinose and glucose. From the obtained results, it was observed the possibility of application of the proposed method in biorefineries, creating an alternative for the reuse of this biomass by the sugar and alcohol industries.